Biological function of the dTDP-rhamnose synthesis pathway in Streptococcus mutans. - Tsukioka, Y (1997)
We have cloned a new gene locus that comprises three genes concerned with the biosynthesis of the serotype c-specific polysaccharide antigen in Streptococcus mutans. The genes encode proteins exhibiting significant homology to the rfbA, rfbB, and rfbD gene products that are involved in the anabolism of dTDP-L-rhamnose from D-glucose-1-phosphate. This anabolism pathway pertains to biosynthesis of the O antigen of lipopolysaccharide in gram-negative bacteria. The cell extract of Escherichia coli expressing each of the cloned genes of S. mutans exhibited enzymatic activity corresponding to the homologous counterpart of the rfb gene products. Rhamnose was not detected in the cell wall preparation purified from the mutant in which each of the three cloned genes was insertionally inactivated. Rabbit antiserum against S. mutans serotype c-specific antigen did not react with the autoclaved extracts from these mutants. These results indicate that the gene products identified in the present study are involved in the dTDP-L-rhamnose synthesis pathway and that the pathway relates to the biosynthesis of the serotype-specific polysaccharide antigen of S. mutans. Southern hybridization analysis revealed that genes homologous to the cloned genes involved in the dTDP-L-rhamnose synthesis pathway were widely distributed in a variety of streptococci. This is the first report of the biological function of the dTDP-rhamnose pathway in streptococci.